Exposure to fluctuating temperatures leads to reduced immunity and to stress response in rattlesnakes - Fabricio-Neto, Ailton [UNESP] (2019)
Ectothermic organisms often experience considerable variation in their body temperature throughout the circadian cycle. However, studies focusing on the measurement of physiological traits are usually performed under constant temperature regimes. This mismatch between thermal exposure in the field and experimental conditions could act as a stressor agent, as physiological functions are strongly influenced by temperature. Herein, we asked the question whether constant thermal regimes would cause a stress response and impact the immunity of the South American rattlesnake (Crotalus durissus) when compared with a fluctuating thermal regime. We addressed this question by determining heterophil:lymphocyte (H:L) ratio, plasma bacteria-killing ability (BKA) and corticosterone (CORT) levels in snakes kept under a constant temperature regime at 30 degrees C, and under a fluctuating regime that oscillated between 25 degrees C at night and 35 degrees C during the day. The experiments had a mirrored design, in which half of the snakes were subjected to a fluctuating-to-constant treatment, while the other half was exposed to a constant-to-fluctuating treatment. The shift from constant to fluctuating thermal regime was accompanied by an increase in plasma CORT levels, indicating the activation of a stress response. Exposure to a fluctuating thermal regime at the onset of the experiments induced a decrease in the BKA of rattlesnakes. H:L ratio was not affected by treatments and, therefore, the shift between thermal regimes seems to have acted as a low-intensity stressor. Our results suggest that removal from temperatures close to the snake's preferred body temperature triggers a stress response in rattlesnakes.